An overview for assessing a number of systems for estimating age and gender of speakers - Aalaa Ahmed Mohammed; Yusra Faisal Al-Irhayim (Tikrit Journal of Pure Science)
The determination of the age and gender of the speaker of the speech signal is an interesting topic in the interaction between human-machine. Speech signal has a variety of applications ranging from speech analyses to allocate human-machine interactions. This paper aims to conduct a comparative study of age and gender classification algorithms applied to the speech signal. Comparison of experimental results of different sources of voices for speakers of different languages and methods of miscellaneous classification such as Bayes classifier, neural network, support vector machines, K-nearest neighbor, gaussien mixture model and hybrid method based on weighted analysis of a directed non-negative matrix and a neural network with a general recession as well as some deep learning methods, is done in order to show different results  to classify the age and gender of the speaker when processing the speech signal. The study showed that methods and algorithms of deep learning have excelled in providing accuracy ratios higher than other methods, and it shows that the hybridization of two or more classification methods increases the accuracy level of the results.